Pendekatan Deep Learning Model Project Based-Learning - Munali, Munali; Dewi, Shinta; Alifah, Siti; Hapsari, Sri (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
The purpose of the Community Service (PkM) activity is to provide socialization on the optimal implementation of the deep learning approach using the project-based learning model in the classroom. Participants in the Community Service with SDN 04 Cimande, Bogor Regency, were 15 educators. Based on a survey with partners, there were several problems faced by partners in the field regarding the socialization of the deep learning approach in the classroom. The problem that occurred for partners was that educators wanted to implement the deep learning approach in the classroom optimally. Through discussions with several educators at SDN 04 Cimande, Bogor Regency, the average educator did not understand the implementation of the deep learning approach using the project-based learning model in the classroom. Based on this information, we from the PkM team of Indraprasta PGRI University will provide training to educators at the school, both theoretically and directly in practice. The PkM activity uses presentation, lecture, discussion, or a combination of these methods. Then, to deepen the material that has been presented, training participants are given the opportunity to ask questions. The success of the PkM activity, educators are given the task of implementing the deep learning approach in the classroom two weeks after the activity. The data collection technique is through Google Forms. The success indicator with the formula of the average score of the mindful learning dimension, the meaningful learning dimension, and the joyful learning dimension is more than or equal to 70%. The results of the PkM: 1) the total average score on the mindful learning dimension is 85%, 2) the total average score on the meaningful learning dimension is 87%, and 3) the total average score on the joyful learning dimension is 100%. The conclusion of the PkM results is that educators at SDN 04 Cimande, Bogor Regency can implement the deep learning approach using the project-based learning model.